Misinformation, visual manipulation and representation of migration on Twitter: analysys of Aquarius Case (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
This work analyzes the role of images as a vehicle for the spread of misinformation related to migration on the social media platform Twitter, as well as the characteristics associated with the images used in such processes. To do this, a corpus composed of 321,585 tweets published during the days when Twitter conversations about the rescue and reception of migrants were most intense was analyzed.Building upon this analysis, the characterization of images used as a support for misinformation on social media is addressed, highlighting examples of different categories and analyzing, using a descriptive-qualitative methodology, how images can be manipulated or taken out of their original context to support false information.The results of this study demonstrate that a significant portion of information about migrations exchanged on Twitter relies on visually-oriented content, with photography being the most commonly used medium. Additionally, the importance of developing verification tools based on reverse image search is emphasized as a key measure to combat misinformation on social media.
Keywords: misinformation; Image; Photography; Twitter; X